Synthesis, characterization and antifungal activity of 4-Halobenzoylthiourea bearing α and β- Alanine - Mohamed, Nor Azanita; Ngah, Nurziana; Darnis, Deny Susanti (2014)
Thiourea) deriva,ves) possess) broad) biological) ac,vi,es) including) an,bacterial) and) an,fungal) ac,vi,es) (Saeed) et# al.,) 2009).) Thus,) in) this) study) six) new) 4Bhalobenzoylthiourea) compounds) bearing) α) and) βBalanine) with) different) halogen) atom) subs,tu,ons) have) been) successfully) synthesized) and) characterized) using) CHNS) microelemental) analysis) and) spectroscopic)methods)including)FTIR,)UVBVis,)and)1HB)&)13CBNMR.) Microelemental) analysis) data) of) the) compounds) were) in) agreement) with) the) calculated) values.) ) The) FTIR) spectra) showed) the) presence) of) important) bands) and) 1HBNMR) and) 13CBNMR) exhibited) the) expected) chemical) shiTs.) An,fungal) screening) has) been)evaluated)by)zone)of)inhibi,on,)MIC)and)MFC)studies)against) C. albicans) and) T. mentagrophytes.) The) antifungal) activity) of) the) compounds) were) related) to) the) presence) of) difference) halogen) atoms) and) also) due) to) α) and) βBalanine) presence) in) the) compounds.)